Developing receptive skills in two modern languages: some facilitating and hindering factors - Baran Ielyzaveta; Fábián Márta; Huszti Ilona; Bárány Erzsébet; Барань Єлизавета; Фабіян Марта; Густі Ілона (Universidad Nacional de Colombia, 2010)
Abstract. This paper reports the findings of a case study that investigated the reading mistakes or miscues made by young EFL learners. These learners were native speakers of Hungarian or Ukrainian. The hypothesis was that there is a difference between the miscues made by Hungarian and Ukrainian learners when reading aloud in English because of the influence of their first language (Hungarian belongs to the Finno-Ugrian language family, while Ukrainian belongs to the Indo-European one; the two languages have different orthographies — Roman and Cyrillic). The research focused on three types of reading miscues: phonetic, lexical and grammatical. Results show that Hungarian learners made less miscues than Ukrainian ones. This is mainly due to the mother tongue influence on the foreign language.
Keywords: listening; reading; receptive skills